2019
DOI: 10.1002/lary.27947
|View full text |Cite
|
Sign up to set email alerts
|

The optimal surgical approach for papillary thyroid carcinoma with pathological n1 metastases: An analysis from the SEER database

Abstract: Objectives/Hypothesis: The definition of large-volume pathologic N1 metastases has been changed in the 2017 version 2 of the National Comprehensive Cancer Network guidelines, leading to a controversy over the optimal surgical approach selection for patients with biopsy-proven papillary thyroid carcinoma (PTC). The aim of this study was to investigate the therapeutic efficacy of total thyroidectomy (TT) and thyroid lobectomy (TL) for these patients.Study Design: Retrospective population-based database analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…al., it has been reported that tumor size, except for angioinvasion, was not a significant predictor for the presence of postoperative risk factors (20). In another study evaluating 906 patients with PTC and pathologic N1 metastasis, it has been reported that total thyroidectomy was associated with better survival outcomes compared to lobectomy in patients with more than five lymph node metastases and metastatic lymph node sizes between 2-5 mm (29). In a Korean study analyzing data from 3282 patients with tumor sizes below 2 cm, it has been found that patients who underwent lobectomy had higher rates of long-term recurrence in cases where the tumor size was larger than 18 mm, there were two or more lymph node metastases, or bilateral tumors were present.…”
Section: Discussionmentioning
confidence: 99%
“…al., it has been reported that tumor size, except for angioinvasion, was not a significant predictor for the presence of postoperative risk factors (20). In another study evaluating 906 patients with PTC and pathologic N1 metastasis, it has been reported that total thyroidectomy was associated with better survival outcomes compared to lobectomy in patients with more than five lymph node metastases and metastatic lymph node sizes between 2-5 mm (29). In a Korean study analyzing data from 3282 patients with tumor sizes below 2 cm, it has been found that patients who underwent lobectomy had higher rates of long-term recurrence in cases where the tumor size was larger than 18 mm, there were two or more lymph node metastases, or bilateral tumors were present.…”
Section: Discussionmentioning
confidence: 99%